2021
DOI: 10.1111/ger.12588
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review: Facilitators and barriers in the adoption of teledentistry among older adults

Abstract: Objective/Background: Access to oral health care among older adults is a key issue in society, which has been exacerbated by social distancing measures and lockdowns during the COVID-19 pandemic. Older adults would greatly benefit from teledentistry, yet little information exists on the enablers and challenges of adopting this technology for use with this group. The aim of this scoping review is to summarise the applications and key factors associated with the adoption of teledentistry among older adults. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 42 publications
(235 reference statements)
0
17
0
Order By: Relevance
“…Ben-Omran et al concluded that there was evidence in favor of using teledentistry in several oral health care services, also emphasizing the need for further research [47]. Similar results were obtained by Hui Xuan Tan et al [48], who identified the most common barriers to widely using TD, such as technical issues, lack of funding, and cognitive impairments.…”
Section: The Use Of Teledentistry For Geriatric Populationsmentioning
confidence: 68%
“…Ben-Omran et al concluded that there was evidence in favor of using teledentistry in several oral health care services, also emphasizing the need for further research [47]. Similar results were obtained by Hui Xuan Tan et al [48], who identified the most common barriers to widely using TD, such as technical issues, lack of funding, and cognitive impairments.…”
Section: The Use Of Teledentistry For Geriatric Populationsmentioning
confidence: 68%
“…This can happen for several reasons, such as improper website management to keep track of users' questions, lack of site updates, dentists are not interested in online activities and does not have time for online consultation, avoid answering questions online as a result of legal challenges. These results are confirmed by the fact while there are many advantages ( Estai et al., 2018 ; Tella et al., 2019 ) to using teledentistry services, barriers and challenges to the use of teledentistry are also present, such as legal, ethical, financial, technical, personal, and management barriers ( Kumar, 2014 ; Tan et al., 2021 ).…”
Section: Discussionmentioning
confidence: 89%
“…Barriers to teledentistry include patients' lack of knowledge about IT, poor and inadequate IT literacy of dentists, unfamiliarity of dentists and patients with technology, limitations in infrastructure (such as poor internet access, lack of hardware, cost and efficiency of equipment), low video quality, audio-video mismatch that can be replaced by direct communication (simultaneous communication), how to Fig. 5 Partner institutions that helped to produce articles related to teledentistry during Covid-19 pandemic found in the WOS database store, send and share patient information, confidentiality and protection of patient information, organizational changes in accepting teledentistry, non-acceptance of teledentistry services by relevant authorities including insurance companies, lack of transparency in reimbursement, non-cooperation of other medical centers, inadequate circulars, cost of installing teledentistry equipment and resistance of dentists to new technologies [3,9,19,20,22,24,25,31].…”
Section: Discussionmentioning
confidence: 99%
“…During Covid-19 pandemic, people have been reluctant to visit dentists due to the fear of infection, and front-line health care workers such as dentists have suffered from severe turmoil, anxiety, poor sleep quality, and increased risk of mental illness [2]. Regulatory agencies have recommended social distancing and home quarantine to prevent close contact between individuals and reduce the spread of infection [3]. The Italian scientific dental association has provided recommendations for the management and triage of patients before and after dental treatment, and acknowledged that by suspending dental care, the number of patients in need of hospitalization may increase in the future, so dentists can only provide emergency services and in other cases, they can treat patients digitally using tools such as telemedicine to ensure patient safety, minimize frequent contact with patient and cut the Covid-19 transmission chain [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation